Political Influencers on YouTube: Business Strategies and Content Characteristics - Fischer, Tasja-Selina (2022)
Young media users increasingly engage with public affairs via social media such as YouTube, where content is increasingly produced by influencers who neither represent established professional news media nor political parties. Although the audience of these channels is already substantial in absolute terms and still growing enormously—making alternative influencers serious competitors to professional journalism—we still know little about their ways of attracting and monetizing audiences, the topics they emphasize, or the specific content they provide. To address this void, the present study examines political videos and their producers on YouTube in an explorative and comparative way for English- and German-speaking YouTube channels. We conducted a content analysis of the five most popular YouTube videos for each of the 20 most successful English- and German-speaking political influencers in 2020. Our analyses show that, although English YouTubers already appear to be more professionalized, similar patterns emerge in both language regions, particularly with regards to increasing efforts to manage microcelebrity status. In terms of content, two main types of political YouTube videos were identified: “partisan mockery” and “engaging education.” Results will be discussed in terms of their implications for political discourse, youth participation, and established journalistic media.